THE MAIN PRINCIPLES OF INSULIN THERAPY - Tomina, O. E. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
The article describes the main indications for insulin therapy, insulin agents and their characteristics depending on the origin, methods of producing and action duration. The article elucidates the methods of insulin injection and injection technique. Also, this article presents the insulin therapy regimen: the conventional and basal-bolus therapy, the daily insulin demand depending on the DM period and its distribution throughout a day. Besides, the article deals with the morning hyperglycemia syndromes, their differential diagnostics and therapeutic approach.